Occurrence of urinary tract infection among children attending Gandaki Medical College Teaching Hospital and Research Center, Pokhara, Nepal - Gautam, G; Regmi, S; Magar, NT; Subedi, B; Sharma, T; Regmi, SM (International Journal of Infection and Microbiology, 2013)
INTRODUCTION: Urinary tract infection (UTI) is considered as the most common bacterial infectious disease seen among the pediatric patients. Most commonly, members of Enterobacteriaceae, particularly uropathogenic strains of E. coli and Enterobacter spp. are the primary causative pathogens of UTI in the different part of the world. Emergence of antimicrobial resistance rates among pathogens recovered from urinary tract infections is an increasing problem in the specific region. MATERIALS AND METHODS: Prevalence and anti microbial susceptibility pattern of the bacterial uropathogens isolated from the children attending Gandaki Medical College Teaching Hospital and Reserch Center (GMC) Nepal. A total of 155 children aged upto 15 years were included in this study. Urine cultures were carried out and the isolates were identified by Gram staining and conventional biochemical methods. Antimicrobial susceptibility testing was performed by disk diffusion method according to the Clinical and Laboratory Standards Institute (CLSI). RESULTS: In the present study 21.3 % of the sample size, showed significant bacterial growth. E. coli was the most frequently occurring pathogen (39.40%), followed by Proteus spp. 21.2%, Citrobacter spp. and Streptococcus faecalis (12.1%) Klebsiella spp. (9.1%), and Staphylococcus aureus and Enterobacter (3.0%). Susceptibility rate of E. coli were 69.2% to Gentamycin and Amikacin, 53.8% to Norfloxacin, 38.4% to Nalidixic acid and Norfloxacin. CONCLUSIONS: Pediatric urine culture isolates were becoming increasingly resistant to commonly used antibiotics. Finally, we suggest that empirical antibiotic selection should be based on knowledge of the local prevalence of bacterial organisms and antibiotic sensitivities rather than on universal guidelines. DOI: http://dx.doi.org/10.3126/ijim.v2i3.8665 Int J Infect Microbiol 2013;2(3):82-86